2017
DOI: 10.21010/ajtcam.v14i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Glycyrrhizin Biomarker in Glycyrrhiza Glabra Rhizome and Baby Herbal Formulations by Validated Rp-HPTLC Methods

Abstract: Background: A simple and sensitive thin-layer chromatographic method has been established for quantification of glycyrrhizin in Glycyrrhiza glabra rhizome and baby herbal formulations by validated Reverse Phase HPTLC method. Materials and Methods: RP-HPTLC Method was carried out using glass coated with RP-18 silica gel 60 F254S HPTLC plates using methanol-water (7: 3 v/v) as mobile phase. Results: The developed plate was scanned and quantified densitometrically at 256 nm. Glycyrrhizin peaks from Glycyrrhiza gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Hence, all these phytochemicals revealed in licorice extract have great therapeutical properties. Previous chemical studies also reported that licorice had phytochemicals includes chalcones, phenols, sterols, saponins, and many others that had strong antioxidant, antibacterial activity, and various others (Alam et al, 2017). Another earlier study showed the presence of phytochemicals steroids, alkaloids, tannins, terpenoids, flavonoids, and others in chloroform extract of Glycyrrhiza glabra (Chandra and Gunasekaran, 2017).…”
Section: Results: Phytochemical Analysis: Biochemical Screeningmentioning
confidence: 93%
“…Hence, all these phytochemicals revealed in licorice extract have great therapeutical properties. Previous chemical studies also reported that licorice had phytochemicals includes chalcones, phenols, sterols, saponins, and many others that had strong antioxidant, antibacterial activity, and various others (Alam et al, 2017). Another earlier study showed the presence of phytochemicals steroids, alkaloids, tannins, terpenoids, flavonoids, and others in chloroform extract of Glycyrrhiza glabra (Chandra and Gunasekaran, 2017).…”
Section: Results: Phytochemical Analysis: Biochemical Screeningmentioning
confidence: 93%
“…Although HPLC remains a primary method, various advanced analytical techniques have been proposed. These encompass semipreparative reversed‐phase HPLC with a photodiode array, 13 ultrahigh‐performance liquid chromatography–tandem mass spectrometry, 14 reversed‐phase high‐performance thin‐layer chromatography, 15 HPTLC, 16 and two‐dimensional quantitative nuclear magnetic resonance 17 . A few of these methods are distinct modifications or advancements of HPLC 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…In modern food production, licorice is widely used in beverages, beer, meat and other foods as sweeteners, antioxidants, antimicrobials, foaming agents and flavor enhancers. It is a recognized food additive in the Europe, the United States and China (Montoro et al, 2011;Di Lorenzo et al, 2015;Li et al, 2016;Xu et al, 2016;Alam et al, 2017;Indhu and Shajahan, 2018). Modern pharmacological studies have shown that licorice has numerous effects, such as anti-inflammatory, antiviral, antibacterial, and immunomodulatory, as well as certain hypoglycemic, anti-obesity, and detoxification effects (Yang et al, 2015;Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%